Development and evaluation of an Android-based multimedia application to promote healthy lifestyles in physical education: A study at State Junior High School 29 Semarang - Pujiyanto, Galang Yusuf; Royana, Ibnu Fatkhu; Wibisana, Muh. Isna Nurdin (Physical Education and Sports: Studies and Research, 2025)
Background: The integration of interactive, technology-based media in Physical Education, particularly for teaching health-related content, remains limited despite its potential to enhance student engagement and learning outcomes. Objectives: This study aims to address this gap by developing and evaluating the effectiveness of an Android-based multimedia learning application, "Healthy Habits," designed to support the delivery of healthy lifestyle materials in Physical Education, Sports, and Health (Physical Education) subjects at the junior high school level. Methods: The research employed a research and development (R&D) approach, involving expert validation from media and content specialists and usability trials with teachers and students. Results: Validation results indicated a "Good" rating from the material expert (average score: 4.05) and a "Very Good" rating from the media expert (average score: 4.24), confirming the application's content quality and technical feasibility. Teacher evaluations also yielded a "Good" rating (average score: 4.07). Student trials produced positive responses, with small group testing receiving a "Very Good" rating (average score: 3.29), which increased to 4.23 ("Very Good") in large group testing. An effectiveness test assessing cognitive, affective, and psychomotor learning outcomes showed an average score of 85.6%, categorized as "Very Good." These findings demonstrate the feasibility and effectiveness of "Healthy Habits" as a digital learning tool for promoting healthy lifestyles in secondary school students. Conclusions: The application offers practical value for educators and curriculum developers seeking to integrate mobile technology into Physical Education. Future studies are encouraged to explore the implementation of this application in varied educational contexts and its potential integration across other subject areas.